KEBIJAKAN AMERIKA SERIKAT TERHADAP PENGARUH IRAN DI KAWASAN AMERIKA LATIN PADA MASA PEMERINTAHAN MAHMOUD AHMADINEJAD TAHUN 2009-2013 - Lija Altapia; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The aim of the research is to explain about the foreign policy of United States in countering Iran’s expansion in Latin America under Ahmadinejad’s administration in second term. Iran has significantly increased its diplomatic ties with Latin America especially the leftist group to counter the imperialism of West and United States. Ahmadinejad looks Latin America as a compatible alliances when the United States and Latin America in high tensions condition and particularly to get a political support with their nuclear program which get sanctions and pressures from United States and its allies such as European Union and United Nation and forcing Iran to stop their nuclear program.The research was conducted using research methods literature where the data and information obtained from sources which are relevant to the research problems. This reasearch uses perspective to analyze nation of United States and Rational Actor theory proposed by Graham T. Allison and the concept of national interest of Jack C. Plano and Roy Olton.This search shows that the policy of the United States to use a comprehensive government-wide strategy to counter Iran’s growing hostile presence and activity in the Western Hemisphere by working together with United States allies and partners in the region to mutually deter threats to United States interests by the Government of Iran, the Iranian Islamic Revolutionary Guard Corps (IRGC), the IRGC’s Qods Force, and Hezbollah.Keywords: Foreing Policy of United States, Iran Nuclear Program, Western Hemisphere, Diplomatic Ties.